FAKTOR-FAKTOR YANG MEMPENGARUHI OPINI AUDIT DENGAN TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN KEMENTERIAN/LEMBAGA SEBAGAI VARIABEL INTERVENING - Adelia Pramita Sari (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2016)
The purpose of this research to analyze the effect audit findings, the follow up of examination result and quality of human resources on the audit opinion with disclosure level of financial statements of the ministries /Instutitions as intervening variable . The quality of human resources variable consist of the capacity of the operator’s financial statement and the educational background of the leadership ministries/instutitions. In addition, this study also analyzes trend diclosure level of financial statements during 2010-2013 . The samples of this research were 74 ministries / Instutitions. Analysis data technical that used in this research is lag effect with ordinary least square for model 1 and ordered logistic for model 2 . the result showed that the audit findings , the folow up of examination result, the capacity of the operator’s financial statements. Howewer, the educational background of the leadership ministries/institutions are proved to have no effect on the audit opinion with the diclosure level of financial statements as intervening variable.